<DATA REPORT>RIOMETER RECORDS OF 30 MHz COSMIC NOISE AT SYOWA STATION, ANTARCTICA IN 1985 - KURATANI, Yasukazu; MAENO, Hideo (National Institute of Polar Research, 1987)
P(論文) departmental bulletin paper